Gendered moods : psychotropics and society - Ettorre, E. M. (Routledge, 1995)
"Tranquillisers are prescribed twice as often to women as men, yet little gender-based research has been carried out on the social context of their use." "Gendered Moods offers the first feminist analysis of the gendered character of psychotropic drug use, based on studies of long-term psychotropic drug users and the content of drug advertising. The authors argue that gender differences in psychotropic drug use are manifestations of the gendered construction of society as a whole, and that, as a result, women are particularly susceptible to being channelled into a state of dependency on prescribed drugs." "Exploring current social scientific debates relating to drug users and providers, Gendered Moods also provides a critical review of previous research, and concludes that gender has been underestimated as an influence on the use and effects of these drugs. It will give a much needed introduction to a neglected area of study."--Jacket